Underlayer materials and friction materials
By integrating a lignin-modified phenolic resin into the underlayer material, the friction members exhibit enhanced strength, heat resistance, and reduced brake squeal, overcoming the challenges faced by previous underlayer materials.
Patent Information
- Application Number
- JP2021125660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-07-30
AI Technical Summary
Existing underlayer materials for frictional members in vehicles face challenges with strength, heat resistance, and noise reduction, particularly in suppressing brake squeal.
Incorporating a plant-derived resin, specifically a lignin-modified phenolic resin, into the underlayer material, which is used in conjunction with a friction material and a pressure plate, to enhance strength, heat resistance, and reduce brake squeal.
The use of plant-derived resin in the underlayer material results in friction members with improved strength, heat resistance, and reduced likelihood of brake squeal, effectively addressing the limitations of previous technologies.
Smart Images

Figure 0007667010000004 
Figure 0007667010000001 
Figure 0007667010000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an underlayer material for friction members used in automobiles, railway vehicles, industrial machines, and the like. [Background technology]
[0002] Conventionally, friction members are required to have various performance characteristics, one of which is to reduce noise (brake squeal) generated during braking.
[0003] As a technology for suppressing brake squeal, for example, Patent Document 1 discloses a friction material consisting of a fiber base material, a binder, an abrasive, and a friction modifier, which is characterized in that the friction modifier contains silane coupling agent-dispersed silicone rubber particles in which a silane coupling agent is dispersed inside silicone rubber particles. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-107205 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, according to the investigations of the present inventors, there are concerns about the reduction in strength and heat resistance in the technique described in Patent Document 1.
[0006] The present invention has been made in consideration of the above-mentioned conventional situation, and has an object to provide an underlayer material that can provide a friction member that has high strength and heat resistance and is less likely to cause brake squeal. [Means for solving the problem]
[0007] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by incorporating a plant-derived resin in an underlayer material, and have thus completed the present invention.
[0008] That is, the present invention provides the following <1> ~ <5> This is regarding. <1> An underlayer material for use in a friction member, The friction member includes a friction material and a pressure plate. The friction material includes a friction modifier, a binder, and a fiber base material, The underlayer material includes a plant-derived resin. <2> The plant-derived resin is a lignin-modified phenolic resin. <1> The underlayer material according to claim 1. <3> The content of the plant-derived resin is 5 to 15% by mass. <1> or <2> The underlayer material according to claim 1. <4> friction material, <1> ~ <3> 13. A friction member comprising: an underlayer material according to any one of claims 1 to 12; and a pressure plate in this order. <5> The friction material does not contain a copper component. <4> The friction member according to claim 1. Effect of the Invention
[0009] A friction member using the underlayer material of the present invention has high strength and heat resistance, and is less likely to cause brake squeal. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the structure of a friction member of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below, however, these are examples of preferred embodiments and the present invention is not limited to the contents thereof.
[0012] The underlayer material of the present invention is used in a friction member.
[0013] [Friction materials] As shown in FIG. 1, a friction member 10 includes a friction material 1, an underlayer material 2, and a pressure plate 3 in this order.
[0014] [Friction material] The friction material includes a friction modifier, a binder, and a fibrous base material.
[0015] <Friction adjustment material> Friction modifiers are used in friction materials to impart desired friction characteristics, such as wear resistance, heat resistance, and fade resistance, to the friction materials.
[0016] Examples of friction modifiers include inorganic fillers, organic fillers, abrasives, lubricants, and metal powders.
[0017] Examples of inorganic fillers include titanates such as potassium titanate, lithium titanate, lithium potassium titanate, sodium titanate, calcium titanate, magnesium titanate, and magnesium potassium titanate, as well as inorganic materials such as barium sulfate, calcium carbonate, calcium hydroxide, vermiculite, and mica. These may be used alone or in combination of two or more.
[0018] The inorganic filler is preferably used in an amount of 30 to 80 mass %, more preferably 40 to 70 mass %, based on the entire friction material.
[0019] Examples of organic fillers include various rubber powders (raw rubber powder, tire powder, etc.), rubber dust, resin dust, cashew dust, tire tread, melamine dust, etc. These may be used alone or in combination of two or more.
[0020] The organic filler is preferably used in an amount of 1 to 15 mass %, more preferably 1 to 10 mass %, based on the entire friction material.
[0021] Examples of the abrasive include zirconium oxide, alumina, silica, magnesium oxide, zirconia, zirconium silicate, chromium oxide, iron oxide trioxide (Fe3O4), chromite, etc. These may be used alone or in combination of two or more.
[0022] The abrasive is preferably used in an amount of 1 to 20 mass %, more preferably 3 to 15 mass %, based on the total mass of the friction material.
[0023] Examples of lubricants include graphite, coke, antimony trisulfide, molybdenum disulfide, tin sulfide, polytetrafluoroethylene (PTFE), etc. These may be used alone or in combination of two or more.
[0024] The lubricant is preferably used in an amount of 1 to 20 mass %, more preferably 3 to 15 mass %, based on the total mass of the friction material.
[0025] Examples of the metal powder include powders of aluminum, tin, zinc, copper, etc. These may be used alone or in combination of two or more.
[0026] The metal powder is preferably used in an amount of 1 to 10 mass %, more preferably 1 to 5 mass %, based on the entire friction material.
[0027] From the viewpoint of imparting the above-mentioned desired friction characteristics to the friction material sufficiently, the friction modifier is used in an amount of preferably 60 to 90 mass %, and more preferably 70 to 90 mass %, of the entire friction material.
[0028] <Binding material> The binder used in the friction material may be any of various commonly used binders, including phenolic resins, various modified phenolic resins such as elastomers, melamine resins, epoxy resins, polyimide resins, and other thermosetting resins.
[0029] Examples of elastomer-modified phenolic resins include acrylic rubber-modified phenolic resins, silicone rubber-modified phenolic resins, nitrile rubber (NBR)-modified phenolic resins, etc. These may be used alone or in combination of two or more.
[0030] From the viewpoint of formability of the friction material, the binder is preferably used in an amount of 1 to 20 mass %, more preferably 3 to 15 mass %, of the entire friction material.
[0031] <Fiber base material> Examples of the fibrous base material used in the friction material include organic fibers, inorganic fibers, etc. The fibrous base materials may be used alone or in combination of two or more kinds.
[0032] Examples of organic fibers include aromatic polyamide (aramid) fibers and flame-resistant acrylic fibers.
[0033] Examples of inorganic fibers include biosoluble inorganic fibers, ceramic fibers, glass fibers, carbon fibers, rock wool, etc. Examples of biosoluble inorganic fibers include biosoluble ceramic fibers such as SiO2-CaO-MgO fibers, SiO2-CaO-MgO-Al2O3 fibers, and SiO2-MgO-SrO fibers, and biosoluble rock wool.
[0034] From the viewpoint of ensuring the strength of the friction material, the fibrous base material is used in an amount of preferably 3 to 30 mass %, and more preferably 5 to 20 mass %, of the entire friction material.
[0035] From the viewpoint of reducing the environmental load, it is preferable that the friction material does not contain a copper component.
[0036] [Underlayer material] The underlayer material of the present invention preferably comprises a friction modifier, a binder and a fibrous base material.
[0037] <Friction adjustment material> Examples of friction modifiers used in the underlayer material include inorganic fillers, organic fillers, abrasives, lubricants, and metal powders.
[0038] Examples of inorganic fillers include titanates such as potassium titanate, lithium titanate, lithium potassium titanate, sodium titanate, calcium titanate, magnesium titanate, and magnesium potassium titanate, as well as inorganic materials such as barium sulfate, calcium carbonate, calcium hydroxide, vermiculite, and mica. These may be used alone or in combination of two or more.
[0039] The inorganic filler is preferably used in an amount of 20 to 50 mass %, more preferably 25 to 45 mass %, of the entire underlayer material.
[0040] Examples of organic fillers include various rubber powders (raw rubber powder, tire powder, etc.), rubber dust, resin dust, cashew dust, tire tread, melamine dust, etc. These may be used alone or in combination of two or more.
[0041] The organic filler is preferably used in an amount of 1 to 15 mass %, more preferably 1 to 10 mass %, based on the entire underlayer material.
[0042] Examples of the abrasive include zirconium oxide, alumina, silica, magnesium oxide, zirconia, zirconium silicate, chromium oxide, iron oxide (Fe3O4), chromite, etc. These may be used alone or in combination of two or more kinds, as required.
[0043] When an abrasive is blended in the underlayer material, the abrasive is preferably used in an amount of 1 to 20 mass %, more preferably 3 to 15 mass %, of the entire underlayer material.
[0044] Examples of lubricants include graphite, coke, antimony trisulfide, molybdenum disulfide, tin sulfide, polytetrafluoroethylene (PTFE), etc. These may be used alone or in combination of two or more kinds, as required.
[0045] When a lubricant is blended in the underlayer material, the lubricant is preferably used in an amount of 1 to 20 mass %, more preferably 3 to 15 mass %, of the entire underlayer material.
[0046] Examples of metal powders include powders of aluminum, tin, zinc, etc. These may be used alone or in combination of two or more.
[0047] The metal powder is preferably used in an amount of 1 to 10 mass %, more preferably 1 to 5 mass %, based on the entire underlayer material.
[0048] The friction modifier is preferably used in an amount of 20 to 70 mass %, more preferably 30 to 60 mass %, of the entire underlayer material.
[0049] <Binding material> The underlayer material of the present invention contains a plant-derived resin as a binder. Plant-derived resins have irregular and extremely complex chemical structures, and as a result, it is believed that a friction member obtained from the underlayer material of the present invention containing a plant-derived resin has high strength and heat resistance and is less likely to cause brake squeal.
[0050] Examples of plant-derived resins include lignin-modified phenolic resins, polylactic acid, esterified starch, polyhydroxybutyric acid, polytrimethylene terephthalate, etc. Among these, from the viewpoint of heat resistance, lignin-modified phenolic resins having functions derived from lignin, which is an irregular and extremely complex chemical structure of polyphenols, are preferred.
[0051] The plant-derived resin is preferably used in an amount of 5 to 15 mass %, more preferably 10 to 15 mass %, of the entire underlayer material. When the content of the plant-derived resin is 5 mass % or more, the strength and heat resistance of the obtained friction member can be further increased, and the occurrence of brake squeal can be further suppressed. When the content of the plant-derived resin is 15 mass % or less, the other components of the underlayer material can be contained in sufficient amounts.
[0052] As other binders used in the underlayer material, various commonly used binders can be used, specifically, thermosetting resins such as phenolic resin, modified phenolic resin, melamine resin, epoxy resin, polyimide resin, etc.
[0053] Examples of modified phenolic resins include acrylic modified phenolic resins, aralkyl modified phenolic resins, silicone rubber modified phenolic resins, nitrile rubber (NBR) modified phenolic resins, etc. These may be used alone or in combination of two or more.
[0054] From the viewpoint of moldability of the underlayer material, the binder is preferably used in an amount of 1 to 25 mass %, and more preferably 5 to 20 mass %, of the entire underlayer material.
[0055] <Fiber base material> Examples of the fiber base material used in the underlayer material include organic fibers, inorganic fibers, etc. Each of the fiber base materials may be used alone or in combination of two or more kinds.
[0056] Examples of organic fibers include aromatic polyamide (aramid) fibers and flame-resistant acrylic fibers.
[0057] Examples of inorganic fibers include steel fibers, biosoluble inorganic fibers, ceramic fibers, glass fibers, carbon fibers, rock wool, etc. Examples of biosoluble inorganic fibers include biosoluble ceramic fibers such as SiO2-CaO-MgO fibers, SiO2-CaO-MgO-Al2O3 fibers, and SiO2-MgO-SrO fibers, and biosoluble rock wool.
[0058] From the viewpoint of ensuring the strength of the underlayer material, the fiber base material is used in an amount of preferably 10 to 50 mass %, and more preferably 15 to 45 mass %, of the entire underlayer material.
[0059] From the viewpoint of reducing the environmental load, it is preferable that the underlayer material does not contain a copper component.
[0060] [Pressure plate] The pressure plate is formed by sheet metal pressing or the like. The material of the pressure plate is not particularly limited, and known iron metal materials can be used. For example, hot-rolled steel sheets for automobile structures such as SAPH400 and SAPH440, and hot-rolled high-tensile steel sheets for automobiles such as SPFH590 can be used.
[0061] [Method of manufacturing friction materials, underlayer materials and friction members] The friction material, underlayer material, and friction member can be manufactured by known manufacturing processes. For example, the above-mentioned components are blended, and the blend is subjected to processes such as preforming, thermoforming, heating, and polishing according to a conventional manufacturing method.
[0062] A method for manufacturing a friction member including a friction material, an underlayer material, and a pressure plate generally includes the following steps. (a) A process of forming a pressure plate into a desired shape using a sheet metal press. (b) A process of degreasing, chemical conversion and primer treatment on the pressure plate, and applying an adhesive. (c) A process in which the raw materials for the friction material and the raw materials for the underlayer material are blended, thoroughly homogenized by mixing, and molded at room temperature under a specified pressure to produce a preform. (d) A thermoforming process in which the preform and the pressure plate coated with adhesive are bonded together by applying a predetermined temperature and pressure (molding temperature: 130 to 180°C, molding pressure: 30 to 80 MPa, molding time: 2 to 10 minutes). (e) After-curing (150-300°C, 1-5 hours) and final finishing such as polishing, scorching, and painting.
[0063] The thickness of the friction material is preferably 4 to 15 mm, and more preferably 6 to 13 mm. The thickness of the underlayer material is preferably 1 to 4 mm, and more preferably 1 to 3 mm. EXAMPLES
[0064] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these in any way.
[0065] (Examples 1 to 3, Comparative Examples 1 to 3) The compounding materials for the friction material and the compounding materials for the underlayer material shown in Tables 2 and 3 were respectively placed in a mixer and mixed at room temperature for 4 minutes to obtain a mixture of the compounding materials for the friction material and a mixture of the compounding materials for the underlayer material.
[0066] The resulting mixture was subjected to the following steps of (i) preforming, (ii) thermoforming, and (iii) heat treatment and scorching to produce a friction material.
[0067] (i) Preforming The mixture of compounded materials for the friction material and the mixture of compounded materials for the underlayer material were placed in a mold of a preforming press and molded at room temperature and 20 MPa for 10 seconds to prepare a preforming body. (ii) Thermoforming This preform was placed in a thermoforming mold, and a metal plate (pressure plate) to which an adhesive had been applied was placed on top of it, followed by heat and pressure molding at 150° C. and 40 MPa for 5 minutes. (iii) Heat treatment, scorch This hot-pressed compact was heat-treated at 250° C. for 3 hours, and then the surface was polished. Next, the surface of this hot-pressed molded product was subjected to a scorch treatment and finished by painting to obtain a friction member.
[0068] The strength, heat resistance, and brake squeal were evaluated by the following methods for the friction members obtained in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Tables 2 and 3.
[0069] <Strength> The shear strength of the friction members was measured at 25°C and 300°C in accordance with JIS D 4422 (adhesive area: 55 cm 2 ). The measured value is the shear force per unit area (N / cm2) calculated by dividing the stress at the time of shear failure by the bonding area between the pressure plate and the underlayer material. 2 ) was decided.
[0070] The calculated shear force was evaluated based on the following criteria.
[0071] (Room temperature) ◎: 550N / cm 2 End ○: 500N / cm 2 More than 550N / cm 2 less than △: 450N / cm 2 More than 500N / cm 2 less than ×:450N / cm 2 less than
[0072] (300℃) ◎: 350N / cm 2 End ○: 300N / cm 2 More than 350N / cm 2 less than △: 250N / cm 2 More than 300N / cm 2 less than ×:250N / cm 2 less than
[0073] <Heat resistance> The friction members obtained above were evaluated using a full-size dynamometer under the test conditions shown in Table 1. That is, fade (speed: 100 → 0 km / h, deceleration: 4.4 m / s 2 10-15 times) and recovery (speed: 50→0km / h, deceleration: 3.0m / s 2 The repeated cycle of this test (15 times at 1000 rpm) caused a sudden thermal change, and it was confirmed whether or not cracks would occur on the side of the friction material due to the difference in thermal conductivity between the friction material and the underlayer material caused by this thermal change.
[0074] Other conditions were as follows: Pad area: 37cm 2 , Disc diameter: 300mm, Inertia: 100kg m 2
[0075] [Table 1]
[0076] The cracks that occurred were evaluated according to the following criteria. ◎: No cracks ○: Cracks less than 0.1 mm wide occurred △: Cracks with widths between 0.1 mm and 0.2 mm have occurred ×: Cracks with a width of 0.2 mm or more have occurred
[0077] <Brake squeal> Using the friction members obtained above, a brake squeal test was carried out on an actual vehicle (vehicle type: SUV AT, vehicle weight: 2000 kg) in accordance with JASO C402 (passenger vehicle brake pad actual vehicle test method) to determine the brake squeal occurrence rate.
[0078] The brake squeal occurrence rate thus obtained was evaluated based on the following criteria. ◎: No squealing ○: Over 0% and less than 5% △: 5% to less than 10% ×: 10% or more
[0079] [Table 2]
[0080] [Table 3]
[0081] The results in Tables 2 to 3 show that the friction members obtained from the underlayer materials according to Examples 1 to 3 have high strength and heat resistance, and are less likely to cause brake squeal. [Explanation of symbols]
[0082] 1 Friction material 2 Underlayer material 3 Pressure Plate 10 Friction material
Claims
1. An underlayer material for use in a friction member, The friction member includes a friction material and a pressure plate. The friction material includes a friction modifier, a binder, and a fiber base material, The underlayer material includes a plant-derived resin.
2. 2. The underlayer material according to claim 1, wherein the plant-derived resin is selected from the group consisting of lignin-modified phenolic resin, polylactic acid, esterified starch, polyhydroxybutyric acid, and polytrimethylene terephthalate.
3. The undergarment according to claim 1 or 2, wherein the content of the plant-derived resin is 5 to 15% by mass. Layer material.
4. An underlayer material described in any one of claims 1 to 3, wherein the friction material does not contain a plant-derived resin.
5. A friction material, an underlayer material according to any one of claims 1 to 4, and a pressure plate. A friction member having, in this order.
6. The friction member of claim 5 , wherein the friction material is copper-free.
Citation Information
Patent Citations
Pad for disc brake
JP1989049725A
Friction material
JP2012107205A
Friction material
JP2013173882A